Room-temperature nonlinear dielectric constants and dielectric tunability in poled Pb(Mg1/3Nb2/3)O3-Pbtio3 single crystals - Chew, Khian Hooi; Luo, H.S.; Zhao, X.Y.; Wang, J.; Chan, W.L.H.; Choy, C.L. (2003)
The room-temperature second-, third- and fourth-order nonlinear dielectric constants of poled (1-x)Pb(Mg1/3Nb2/3) O3-xPbTiO3 single crystals were determined by measuring the dielectric response at a frequency of 10 kHz and under a dc bias of 0-1000 V/mm. Tunability of the apparent dielectric constant εr was also defined and examined. The results show the phase structure, domain state, composition and orientation dependences of the dielectric nonlinearity and tunability. It is also shown that the 〈011〉-poled monodomain orthorhombic ferro-electric 0.67 Pb(Mg1/3Nb2/3)O3-0.33 PbTiO3 single crystal has the largest nonlinear dielectric constants and the highest tunability of εr in the monodomain crystals. It could be a most promising candidate for applications where a high dielectric nonlinearity is needed.